The Effect Of Team Quiz Assistant Method Of Question Card Medion Mathematics Learning Outcomes - Ramadhani, Balgis Riski (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the team quiz method with the help of question card media on the mathematics learning outcomes of third grade students at SD Negeri Gondosuli 1, Muntilan District. This study uses a quantitative approach with a pre- experimental design type one group pretest posttest design with a total sample of 19 students who received treatment in the form of a team quiz method assisted by a question card media. Data collection techniques in the form of tests (pretest and posttest) to reveal student learning outcomes and observation sheets to reveal the implementation of the team quiz method. Validity test using Product Moment correlation with valid results of the pretest 29 items and the posttest 32 items. The reliability test used Chronbach's Alpha with the results on the pretest 0.963 and the posttest 0.962. The data analysis technique in this study used the Kolmogorov-Smirnov analysis prerequisite test and showed a result of 0.200 on the pretest and 0.129 on the posttest. Hypothesis testing using Paired sample t-test. The results of this study indicate that there is an increase in the average pretest and posttest results before and after being given treatment using the team quiz method with the help of question card media. The average pretest value before treatment was 62 while the posttest value after treatment was 79. The results of the analysis of the Paired sample t-test test showed a significance value of 0.001 (less than 0.05). So it can be concluded that the team quiz method with the help of question card media has an effect on mathematics learning outcomes.